Exploring the processes of parenting in the context of multidimensional poverty when children demonstrate behavioural problems: a single case study in post-1994 Apartheid South Africa - Cilliers, Nicola (Department of Health and Rehabilitation Sciences, 2025)
Background: Families are acknowledged in South African and international policy as the cornerstone of a healthy society, with parenting increasingly becoming the focus of occupational therapy intervention for children's behavioural problems. However, emerging literature from the South suggests pervasive structural and situational challenges in which parenting unfolds and must be navigated. Current conceptualisations of parenting within and beyond occupational science are left wanting with regards to understanding how parenting unfolds in these challenging contexts. Different knowledge(s) about how parenting might unfold in diverse contexts are required to inform more responsive support of families in the margins. Aim: This study sought to explore and describe the occupation of parenting when children demonstrate behavioural problems in the context of multidimensional poverty in post-1994 South Africa. This context presents with complex challenges that align well with the study's intention to contribute knowledge from the Global South. Methodology: Drawing upon a post-structuralist paradigm, the study adopted a qualitative single, intrinsic case study design. Data was collected over a 6-month period with two families, recruited purposively. They resided in the same geographical community, where many experienced several markers of poverty, and self-identified as having children with behavioural difficulties. Individual, in-depth narrative interviews served as the primary data collection method, in conjunction with several secondary data sources. Data was analysed using a narrative analytic process and direct interpretation of data sources. Findings: One overarching assertion comprising of two core assertions emerged, revealing that parenting unfolds dynamically as a process of relational emergence. This process is more and less consciously, intergenerationally and contextually enmeshed as caregivers engage with and through iterative relational complexities. Caregivers wrestle with their enmeshment in dominant discourses and practices as they work to resist and adapt these, but also often reproduce them. This wrestling shapes and is shaped by the relational agency of caregivers, children and community members as they influence and respond to everyday parenting situations. Children's behavioural problems did not emerge as a determinant of parenting practices, functioning rather as part of the relational context in which parenting unfolds. Discussion and Conclusion: Parenting as a process of relational emergence is discussed as a possible lens for understanding parenting in the margins, drawing on theories of collective occupation and occupational choice to unpack how intentionality and practical sense might operate within this process. Parenting's complexities demand further research to understand how it truly unfolds in diverse contexts and should be a focus area in undergraduate occupational therapy programmes. Parenting may be further supported in practice through appreciating plurality in parenting knowledge and experiences, and considering parenting's complexities in how support services are developed and appraised.